2010
DOI: 10.3147/jsfp.45.43
|View full text |Cite
|
Sign up to set email alerts
|

Serological Characterization of Edwardsiella ictaluri Strains Isolated from Wild Ayu Plecoglossus altivelis

Abstract: E d wa r d s i e l l a i c t a l u r i , a me mb e r o f t h e f a mi l y E n t e r o b a c t e r i a c e a e , i s t h e c a u s a t i v e a g e n t o f e n t e r i c s e p t i c e mi a o f c a t f i s h ( ESC) 1 ) wh i c h i s r e c o g n i z e d a s o n e o f t h e mo s t s i g n i f i c a n t c a u s e s o f mo r b i d i t y a n d mo rt a l i t y i n c u l t u r e d c h a n n e l c a t f i s h I c t a l u r u s p u n c t a t u s i n s o u t h e a s t e r n Un i t e d S t a t e s 2 ). A l t h o u g h E . i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Indeed, a more recent study was able to demonstrate the existence of a distinct serogroup present within E . ictaluri isolates from diseased wild ayu in Japan and P. hypophthalmus from Indonesia and Vietnam compared with the type strain (Hassan et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a more recent study was able to demonstrate the existence of a distinct serogroup present within E . ictaluri isolates from diseased wild ayu in Japan and P. hypophthalmus from Indonesia and Vietnam compared with the type strain (Hassan et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that E . ictaluri species is composed of host‐specific genotypes that exhibit both serological and antigenic heterogeneity which make the serum specific to immunogenic epitopes from one host have reduced antibody activity when an encounter with the isolates from other hosts occurs (Griffin et al, 2016; Hassan et al, 2010; Lobb et al, 1993; Machimbirike et al, 2021; Panangala et al, 2006; Plumb & Klesius, 1988; Rogge et al, 2013) making the available vaccines to be restricted and host specific to channel catfish and striped catfish. A vaccine with high efficacy for the protection of tilapia is still lacking, as well as a cross‐protection vaccine for all susceptible hosts in aquaculture (Kayansamruaj et al, 2020; Klesius & Shoemaker, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The exist (Kordon et al, 2020;Yang et al, 2016). Research has shown that E. ictaluri species is composed of host-specific genotypes that exhibit both serological and antigenic heterogeneity which make the serum specific to immunogenic epitopes from one host have reduced antibody activity when an encounter with the isolates from other hosts occurs (Griffin et al, 2016;Hassan et al, 2010;Lobb et al, 1993;Machimbirike et al, 2021;Panangala et al, 2006;Plumb & Klesius, 1988;Rogge et al, 2013) making the available vaccines to be restricted and host specific to channel catfish and striped catfish.…”
Section: Discussionmentioning
confidence: 99%
“…In South‐East Asia (SEA), the major freshwater aquaculture species produced are topped by tilapia and catfishes (20% and 18%, respectively, by quantity in 2014) (Kayansamruaj et al., 2020; SEAFDEC, 2017); hence, mortalities due to E. ictaluri infections in these hosts can result in substantive economics losses and threaten food security. Interestingly, earlier research has shown that E. ictaluri species is composed of host‐specific genotypes that exhibit both serological and antigenic heterogeneity whereby serum specific to immunogenic epitopes from one host had reduced antibody activity to isolates from other hosts (Griffin et al., 2016; Hassan et al., 2010; Lobb et al., 1993; Panangala et al., 2006; Plumb & Klesius, 1988; Rogge et al., 2013). Genetic variations were also evident with the failure of E. ictaluri isolates from different hosts to cross‐infect other susceptible hosts as well as lack of cross‐protection when one host is immunized with an isolate from a different host (Klesius & Shoemaker, 1997; Rogge et al., 2013; Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%